2006
DOI: 10.1007/s00261-005-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Bladder tumors: virtual MR cystoscopy

Abstract: Virtual cystoscopy is a promising new technique based on computer-simulated rendering of the inner surface of the urinary bladder using volumetric magnetic resonance (MR) imaging data, thus enabling maneuvers that normally are not possible with conventional cystoscopy. Due to several distinct advantages over conventional cystoscopy such as minimal invasiveness, evaluation of the urethral orifice from a cranial point of view and an opportunity to observe diverticula formations and the inner urethral space, gado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Authors compared these reconstructed images to conventional imaging methods revealing efficacy at a similar level (32,36,37). Moreover, due to more detailed data on periurethral tissue provided by MRU, it may play a vital role in postoperative assessment of treatment effects, in particular in post-traumatic patients with posterior urethra stricture in whom the outcomes of surgical treatment are not satisfactory.…”
Section: Mri In Assessment Of Anterior Urethral Stricturesmentioning
confidence: 99%
“…Authors compared these reconstructed images to conventional imaging methods revealing efficacy at a similar level (32,36,37). Moreover, due to more detailed data on periurethral tissue provided by MRU, it may play a vital role in postoperative assessment of treatment effects, in particular in post-traumatic patients with posterior urethra stricture in whom the outcomes of surgical treatment are not satisfactory.…”
Section: Mri In Assessment Of Anterior Urethral Stricturesmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the bronchi, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,6,8,10,11,16,19,21,23,24). Shigematsu et al (20) reported the use of virtual intravascular MR endoscopy for aneurysms in three cases.…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the tracheobronchial tree, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,(6)(7)(8)10,11,16,19,21,23,24). Virtual endoscopy used for preoperative planning in neurosurgery for endoscopic third ventriculostomy, nasal cavity and paranasal sinus surgery, and virtual endoscopy visualization of the sphenoid sinus and important adjacent structures is valuable for training and the preoperative planning of endonasal transsphenoidal surgery (15).…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of bladder cancer is extremely important. With recent advances in imaging and visualization techniques, virtual cystoscopy (VCy), which is based on volumetric computed tomography (CT) or magnetic resonance (MR) imaging data, has revealed its potentials for detecting bladder abnormalities [2]. As reported in [3], bladder cancerous tissue invades gradually from the mucosa into the wall muscles, inducing morphological changes and texture changes in the bladder wall.…”
Section: Introductionmentioning
confidence: 99%